A diacronia e a sincronia no(s) curso(s) de Linguística Geral: dos cursos à edição - Giembinsky, Mariane Silva e Lima (2019)
This dissertation was developed with the objective of investigating the elaboration of Ferdinand de Saussure, a 20th century linguist who brought a new point of view to Linguistics, allowing Linguistics to become a modern science. First, we present the nineteenth-century studies that were based on the diachronic point of view, through the comparisons of languages, emphasizing the research of Rask, Boop, Grimm and Schleicher. This investigation was important so that we could verify the process of distancing Saussure's ideas from contemporary linguists. Saussure began his work as a comparator by studying the vowel system in the Indo-European in 1878. In that year, he published in Leipzig the Work on the Primitive System of the Indo-European Vowels and On the Absolute Genitive in Sanskrit in 1880. However, the genevan author was ahead of his time, and from his many questions shows us a new perspective on the studies of language: the synchrony. The result of his reflections, in the form of teachings, was only presented to the public after his death with the publication of the Course in General Linguistics, posthumous work, published in 1916, by alumni and colleagues of Ferdinand de Saussure, Bally and Sechehaye. They gathered a few handwritten sheets by the professor himself and notes from the students who attended the three general linguistics courses between 1907 and 1911 at the University of Geneva. Thus, based on a comparative analysis between the students' books that participated in the courses and the edition of the book Course in General Linguistics, we sought to point out the course of elaboration of Saussure's theorization about the conceptual pair diachrony and synchrony. Afterwards, we present the question of order regarding these perspectives on the language, because the editors chose not to follow the same order of presentation of the content of Saussure's classes; so we raised the following hypothesis: was there a distortion of the teachings of the Genevan master due to the fact that the Course in General Linguistics did not follow the order of the courses taught? In order to answer this question in our research, we initially used the Course in General Linguistics and the students' notebooks that attended the master classes, edited by Eisuke Komatsu, George Wolf and Roy Harris, so that we could compare the order of exposure of the concepts of diachrony and synchrony in both the edition and the notebooks of the students. In addition, we present the critical issues that allowed us to verify a new way of looking at the issue of the order of the courses and the edition, mainly the critical edition of Tulio de Mauro. In addition, we explored linguists who spoke about this issue in the CLG in order to verify if there was distortion of the teachings of the master genevan during this course of elaboration.